A model of marketing-driven innovation in lifestyle tourism businesses - Machado, M.; Dias, Á.; Patuleia, M.; Pereira, L. (Journal of Tourism, Heritage and Services Marketing, 2025)
Purpose: The research investigates the direct and indirect effects of marketing capabilities on innovation in lifestyle tourism businesses. It also explores the mediating effects of entrepreneurial self-efficacy, intense positive emotions, and proactivity affect lifestyle entrepreneurship. Methods: To test the conceptual model survey data were used with a sample of 187 entrepreneurs operating in lifestyle tourism in Portugal. The model was examined using a Partial Least Squares Structural Equation modelling (PLS-SEM). Results: It was found that marketing capabilities’s impact on innovation is direct and indirect, showing that entrepreneurial self-efficacy, positive emotions, and proactivity play a key part in the link between marketing capabilities and innovation. Implications: By adding self-efficacy, emotions, and proactivity to the effects of marketing on innovation, the study advances the study on lifestyle entrepreneurship in tourism. In particular, the study highlights the key role of self-efficacy, emotions, and proactivity. This research describes important characteristics of lifestyle tourism entrepreneurs, providing important insights regarding psychological and behavioural factors mediating the link between marketing capabilities and innovation.